Integrating the Impact of Digital Media and Social Networks on Human Communication and Behavior - Jehlani, Haoniyao (Journal of Public Representative and Society Provision, 2021)
This study aimed to investigate the impact of social media and other forms of online communication on individual and group dynamics. The study used a mixed method, where data were collected through a survey of 500 individuals and semi-structured interviews with 20 participants. This methodology allowed the study to gain a comprehensive picture of the impact of digital media on mental health, online activism, digital citizenship, and social media addiction. The results showed that digital media has both positive and negative impacts on users, with the majority of participants acknowledging the importance of online activism as a tool for social change and digital citizenship as an important aspect of safe and ethical use of digital technology. The study also found that social comparison was a significant factor in social media addiction and negative effects on mental health. These findings emphasize the importance of digital literacy and monitoring online behavior in order to use digital media positively.